Investigação das propriedades ópticas e fotocatalíticas de materiais a base de fosfato de prata - Pereira, Wyllamanney da Silva (Universidade Federal de São Carlos, 2019)
The semiconductor-based photocatalytic degradation of synthetic dyes has been considered a promising approach in wastewater treatment. The main objective in this doctoral thesis was the investigation on structural, morphological, optical and photocatalytic of silver phosphate-based materials. Thus, silver phosphate (Ag3PO4), Ag3-2xCuxPO4 (x = 0.00, 0.01, 0.02, 0.04 and 0.08) solid solutions and silver pyrophosphate (Ag4P2O7) were synthesized by the chemical coprecipitation method (CP) at room temperature. Ag4P2O7 was also prepared by decomposing the silver (I) diamine complex by both CP at 90 °C and hydrothermal methods, conventional (CH) and microwave (MH), at 100, 120 e 140 °C. In addition, silver bromide and silver phosphate composites (AgBr/Ag4P2O7) with different Br/P molar ratios were prepared by using the in situ anion-exchange method at room temperature. For Ag3-2xCuxPO4 (x = 0.00, 0.01, 0.02, 0.04 and 0.08) solid solutions, the results showed that the body centered cubic phase was successfully obtained. The increase in the concentration of Cu2+ ions was able to reduce the average particle size as well as decrease the photocatalytic activity of the pyrophosphates in the degradation of rhodamine B under visible light irradiation. Ag4P2O7 with hexagonal phase, synthesized by the CP, was active in the degradation of RhB and 6G rhodamine by presenting velocity constants of 0.057 and 0.184 min-1, respectively. In relation to the decomposition of silver (I) diamine complex, the synthesis conditions employed in CP, CH and MH methods (from 100 to 120 ° C) influenced the morphological aspects of Ag4P2O7 microparticles; however, the photoluminescence emissions of these materials were similar. Finally, the increase of Br/P molar ratio in AgBr/Ag4P2O7 composites affected in the degradation of RhB. A more detailed study on the structural, morphological and photocatalytic stability was performed for the composite with the highest Br/P molar ratio.
Investigation of optical and photocatalytic properties of silver phosphate-based materials
Keywords: Fotocatálise; Fololuminescência; Rodamina; Pirofosfato de Prata; Photocatalysis; Photoluminescence; Rhodamine; Silver pyrophosphate; Silver phosphate; CIENCIAS EXATAS E DA TERRA::QUIMICA